Penggunaan Batang Napier Operasi Perkalian Dan Pembagian Untuk Mengetahui Kemampuan Pemahaman Konsep Siswa - Yenni, Rika Firma; Malalina, Malalina (Universitas Muhammadiyah Palembang, 2019)
The purpose of this study was to determine the ability of students to understand the concept of using Batang Napier in multiplication and division operations as well as students who obtained conventional learning, while also looking at the influence of the use of Batang Napier on students' conceptual comprehension abilities. This study uses an experimental method that applies two learning models, namely the use of Batang Napier and conventional learning. The population in this study were fourth grade students of MI Al-Hilaliyah Palembang. Sampling uses random sampling techniques, from 2 sample classes totaling 40 students. Where 20 students for the experimental class and 20 students for the control class. The instrument used is a test of conceptual comprehension ability. Learning outcomes data were tested using hypothesis testing, namely the t-test. Then, the value of tcount = 8.77 and ttable = 1.684 is obtained. Because tcount = 8.77> ttable = 1.684 then H0 is rejected and H1 is accepted. So it was concluded that there was an influence on the use of Batang Napier on the ability to understand the concept of fourth grade students of MI Al-Hilaliyah Palembang. The influence shown is a positive influence because the average experimental class learning outcomes (84.9) is greater than the average learning outcomes of the control class (52.2). In other words the ability to understand the concepts of students who use Batang Napier is better than those who get conventional learning.